Effectiveness of commercial video gaming on fine motor control in chronic stroke within community-level rehabilitation. (6th November 2015) - Paquin, Kate; Ali, Suzanne; Carr, Kelly; Crawley, Jamie; McGowan, Cheri; Horton, Sean
Abstract: Purpose : The purpose of this study was to investigate the effectiveness of commercial gaming as an intervention for fine motor recovery in chronic stroke. Methods : Ten chronic phase post-stroke participants (mean time since CVA = 39 mos; mean age = 72 yrs) completed a 16-session program using the Nintendo Wii for 15 min two times per week with their more affected hand (10 right handed). Functional recovery (Jebsen Hand Function Test (JHFT), Box and Block Test (BBT), Nine Hole Peg Test (NHPT)), and quality of life (QOL; Stroke Impact Scale (SIS)) were measured at baseline (pre-testing), after 8 sessions (mid-testing) and after 16 sessions (post-testing). Results : Significant improvements were found with the JHFT, BBT and NHPT from pre-testing to post-testing ( p  = 0.03, p =  0.03, p =  0.01, respectively). As well, there was an increase in perceived QOL from pre-testing to post-testing, as determined by the SIS ( p =  0.009). Conclusion : Commercial gaming may be a viable resource for those with chronic stroke. Future research should examine the feasibility of this as a rehabilitation tool for this population. Implications for Rehabilitation: Stroke survivors often live with lasting effects from their injury, however, those with chronic stroke generally receive little to no rehabilitation due to a perceived motor recovery plateau. Virtual reality in the form of commercial gaming is a novel and motivating way for clients to complete rehabilitation. The Nintendo Wii may be a feasible device to improve both functional ability and perceived quality of life in chronic stroke survivors.